Ripretinib in Advanced Gastrointestinal Stromal Tumors: A Case Series and Literature Review from a Tertiary Cancer Center in India - Neelima, Ventrapragada; Sahni, Shubham; Bharadwaj, Mangu Srinivas; Shamim, Shamim Ahmed; Rastogi, Sameer (Indian Journal of Medical and Paediatric Oncology, 2025)
The therapeutic armamentarium for advanced gastrointestinal stromal tumors (GISTs) is rapidly evolving and demands personalized strategies due to its increasing complexity. We are witnessing an expansion of the treatment modalities with new molecules being added to the same. Novel agents such as avapritinib and ripretinib have been granted Food and Drug Administration approval for platelet-derived growth factor α-D842V-mutant and refractory GIST patients, respectively. Ripretinib received its approval in May 2020 for individuals with advanced GIST who had been treated with three or more kinase inhibitors after publication of results of the INVICTUS trial. Here, we share our experience of four patients with previously treated advanced GIST who received ripretinib through an expanded access program. Our favorable experience with ripretinib warrants wider availability and easy accessibility of this drug in India for improving outcomes of patients with GIST.
Keywords: advanced GIST; ripretinib; case series